The economic crisis: Testing employee relations. (May 2015) - Larsen, Trine P; Navrbjerg, Steen E
Company based bargaining during the recent economic crisis has been subject to some research, but little is known about how this affects employee relations. This article addresses this literature gap by examining the employee relations in companies highly affected, less affected and not affected by the crisis. It argues that although Danish shop stewards are involved in developing local responses to the crisis, most manage to keep their colleagues onboard, even if decisions concern reduced earnings and dismissals. However, a limit exists to the collaboration: in companies hardest hit by the crisis shop stewards are more likely to find conflicts of interests between management and colleagues stressful and fewer feel respected by colleagues. Therefore, shop stewards' engagement in local bargaining comes at a cost and may jeopardize their relations with colleagues. The analysis also reveals that shop stewards from time to time have to cooperate and engage in conflicts with management as well as colleagues as part of local bargaining.